2020
DOI: 10.1002/jmv.26091
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus alternative reading frame protein (ARFP): Production, features, and pathogenesis

Abstract: Earlier observation suggests that hepatitis C virus (HCV) is a single‐stranded RNA virus which encodes at least 10 viral proteins. F protein is a novel protein which has been discovered recently. These studies suggest three mechanisms for the production of this protein concerning ribosomal frameshift at codon 10, initial translation at codons 26 and 85 or 87. In this study, the association between protein F and chronicity of hepatocellular carcinoma (HCC) has been reviewed. Evidence suggests that humoral immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…An RNAseq analysis revealed that the mRNA expression level of the TbX21 gene increased after the treatment in many patients with SVR; however, a significant difference was not observed due to the insufficient number of cases analyzed ( Figure S5 ). TbX21 has been shown to downregulate the expression of PD-1 in lymphocytes [ 19 ], while the expression of TbX21 was downregulated by the F protein produced by HCV [ 20 , 21 ]. F protein, a novel protein, is the product of an alternative reading frame (ARF) of the HCV polyprotein frame.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An RNAseq analysis revealed that the mRNA expression level of the TbX21 gene increased after the treatment in many patients with SVR; however, a significant difference was not observed due to the insufficient number of cases analyzed ( Figure S5 ). TbX21 has been shown to downregulate the expression of PD-1 in lymphocytes [ 19 ], while the expression of TbX21 was downregulated by the F protein produced by HCV [ 20 , 21 ]. F protein, a novel protein, is the product of an alternative reading frame (ARF) of the HCV polyprotein frame.…”
Section: Resultsmentioning
confidence: 99%
“…The HCV-derived F protein has been reported to contribute to the persistence of HCV infection, which may cause hepatic damage and, ultimately, carcinogenesis [ 21 , 28 , 29 ] and through the PD-1/PD-L1 pathway to induce T cell dysfunction: accelerating cell apoptosis and impairing T cell proliferation [ 30 ]. To clarify whether the F protein influences the expression of PD-1, our synthesized F protein was incubated with PBMCs collected from three representative cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…ARFs (such as overprinted ORFs) feature an overall low synonymous divergence [101][102][103] , and are therefore expected to be relatively constrained from accumulating mutations (as mutations in these regions are likely to disrupt more than one viral protein). Importantly, proteins encoded by ARFs have been shown to be abundantly synthesized during infections [104][105][106][107] and can be efficiently processed through class-I MHC processing pathways and induce cytotoxic T lymphocyte responses [108][109][110] .…”
Section: Arfs As Vaccination Targetsmentioning
confidence: 99%
“…Moreover, many positive-sense RNA viruses, which infect mammalian cells, present Alternative Reading Frame Proteins (ARFPs) in their genomes, which are also translated. The existence of such ARFPs poses some questions concerning their role during the infection since they do not directly affect the viral replication in the cell-based infection systems but may contribute to virus replication in vivo, during natural infection, thus representing virulent factors [ 13 ]. One such ARFP is an alternative open reading frame (ORF) overlapping the Core coding region in the +1 frame of genotype 1 and synthesizing another viral protein by a ribosomal frameshift mechanism within an A-rich area.…”
Section: Introductionmentioning
confidence: 99%